Star Trek, Nemesis [videorecording (DVD)] - Berman, Rick; Spiner, Brent; Stewart, Patrick, 1940-; Frakes, Jonathan; Burton, LeVar; Dorn, Michael, 1952- (Paramount Home Entertainment, 2003)
Called to the neutral zone to help negotiate peace between the Romulans and the Federation, Picard and the crew of the Enterprise are confronted by the mysterious new Romulan Praetor Shinzon, a man who claims to be Picard's clone, and who plans to lead a Romulan attack on the Federation.